Distribution and accumulation of metals and metalloids in planktonic food webs of the Mediterranean Sea (MERITE-HIPPOCAMPE campaign). (January 2023) - Chifflet, Sandrine; Briant, Nicolas; Tesán-Onrubia, Javier Angel; Zaaboub, Noureddine; Amri, Sirine; Radakovitch, Olivier; Bǎnaru, Daniela; Tedetti, Marc
Abstract: Particle-size classes (7 fractions from 0.8 to 2000 μm) were collected in the deep chlorophyll maximum along a Mediterranean transect including the northern coastal zone (bays of Toulon and Marseilles, France), the offshore zone (near the North Balearic Thermal Front), and the southern coastal zone (Gulf of Gabès, Tunisia). Concentrations of biotic metals and metalloids (As, Cd, Cr, Cu, Fe, Mn, Ni, Sb, V, Zn) bound to living or dead organisms and faecal pellets were assessed by phosphorus normalisation. Biotic metals and metalloids concentrations (except Cr, Mn, and V) were higher in the offshore zone than in the coastal zones. In addition, biotic Sb and V concentrations appeared to be affected by atmospheric deposition, and biotic Cr concentrations appeared to be affected by local anthropogenic inputs. Essential elements (Cd, Cu, Fe, Mn, Ni, V, Zn) were very likely controlled both by the metabolic activity of certain organisms (nanoeukaryotes, copepods) and trophic structure. In the northern coastal zone, biomagnification of essential elements was controlled by copepods activities. In the offshore zone, metals and metalloids were not biomagnified probably due to homeostasis regulatory processes in organisms. In the southern coastal zone, biomagnification of As, Cu, Cr, Sb could probably induce specific effects within the planktonic network. Highlights: Bioaccumulation of metals and metalloids in the Mediterranean planktonic food webs Determination of biotic metal concentrations by P-normalisation Essential elements are controlled by nanoeukaryotes and copepods Anthropogenic inputs influence the biomagnification of non-essential elements